2014
DOI: 10.1017/jns.2014.45
|View full text |Cite
|
Sign up to set email alerts
|

Body condition of dogs fed diets containing soya hulls

Abstract: Obesity is a growing problem in dogs. Therefore, there is an increasing need of foods for obese dogs with high-fibre content to dilute energies and to reduce energy absorption. Soya hulls are cheap and are widely available as a fibre source. We aimed at evaluating the body condition of dogs fed diets containing 0 % soya hulls (0SH) or 16 % soya hulls (16SH) in replacement of maize. Twelve adult dogs, with 11·3 (se 1·6) kg average body weight (BW), 4·1 (se 0·1) years old and body condition score (BCS) between 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…In two studies, obese or overweight dogs with restricted energy intake showed decreased body weight and body condition scores (BCS) over two months [2,13]. Methods of energy restriction include changing the macronutrient composition, such as high-protein high-fiber diets [14][15][16][17] or high-protein medium-carbohydrate diets [18], and the use of nutritional additives [19,20] or high fiber or polysaccharides [21][22][23][24]. During high-fat-diet-induced canine obesity modeling, research showed changes in glucose homeostasis, the gut microbiota and the metabolome [25][26][27][28][29].…”
mentioning
confidence: 99%
“…In two studies, obese or overweight dogs with restricted energy intake showed decreased body weight and body condition scores (BCS) over two months [2,13]. Methods of energy restriction include changing the macronutrient composition, such as high-protein high-fiber diets [14][15][16][17] or high-protein medium-carbohydrate diets [18], and the use of nutritional additives [19,20] or high fiber or polysaccharides [21][22][23][24]. During high-fat-diet-induced canine obesity modeling, research showed changes in glucose homeostasis, the gut microbiota and the metabolome [25][26][27][28][29].…”
mentioning
confidence: 99%